Pneumomediastinum caused by occult paraquat poisoning: Case report - Deng, Peng (Medicine (Baltimore), 2018)
RATIONALE: Paraquat is a widely applied contact herbicide that is highly poisonous. About 20% of patients with paraquat poisoning develop pneumomediastinum as a complication with a mortality rate of almost 100%. PATIENT CONCERNS: A 15-year-old boy presented with a 1-month history of retrosternal chest pain with no obvious cause. High-resolution computed tomography showed pneumomediastinum. DIAGNOSES: After all likely causes of pneumomediastinum were eliminated, the diagnosis of occult paraquat poisoning was made when serum paraquat concentration was revealed at 467.40 ng/mL, despite the patient's denial of ingestion or contact. INTERVENTIONS: Hemoperfusion, intravenous glucocorticoid, and ulinastatin was administered for 3 days with other routine treatment against paraquat poisoning. The serum paraquat concentration decreased to zero. OUTCOMES: Despite the general high mortality and poor prognosis of paraquat poisoning, the patient recovered and was completely asymptomatic at his 3-month follow-up. LESSONS: Paraquat poisoning should be suspected as a differential diagnosis when patients present with pneumomediastinum without recognizable cause.